Residential archetypes in urban energy simulation models in Chile: Determining factors of residential energy consumption - Aguilera, Francisca; Ossio, Felipe (Revista de la Construcción. Journal of Construction, 2017)
The national and international overview has shown that residential energy consumption is increasing. As a result, efforts have focused on reducing the initial demand for housing and its associated consumption. One of the most used tools for this purpose is bottom-up energy modelling, specifically on the archetypes branch. This method proposes that energy demand of a dwelling can estimated from the interaction of several parameters and factors. However, the method’s main limitation, is the complexity of defining the variables and factors to be used. This article presents a review of specialized literature, concerned with, determining and characterizing residential archetypes. From this literature, It was possible to determine the most influential factors in energy consumption. The results showed 19 factors that were categorized into five groups; general, geometric, thermal, operational, and systems and equipment characteristics. The applicability of these factors to Chile was verified. This article, is intended a guide to generating representative archetypes and characterizing dwellings in an efficiente manner.